PENGARUH KUALITAS PELAYANAN DAN SASARAN KESELAMATAN PASIEN TERHADAP KEPUASAN PASIEN RUMAH SAKIT PRIMA HUSADA MALANG - faizatul muawanah (MAGISTER MANAJEMEN UNISMA, 2020)
Quality of health services can be defined as the degree of perfection of hospital services to meet the needs of the community for health services in accordance with professional standards and service standards by appropriately using appropriate, efficient, and effective hospital resources provided and safe and satisfactory in accordance with the norm , Ethics, law, and socio-culture with due regard to the limitations and capabilities of hospitals and communities.The purpose of this study is to determine the Effect of Service Quality and Target Patient Safety of Patient Satisfaction at Prima Husada Hospital Malang. Design This research is explanatory research with multiple linear regression approach with total sample of 100 respondents (patient and companion of inpatient) Prima Husada Hospital. The study was conducted from May to July 2017.The results showed that the regression coefficient of service quality variables (B1) is known at 0.110 which indicates the magnitude of the effect of service quality variable on patient satisfaction. The result of the regression coefficient means that service quality has an effect of 0.110 on patient satisfaction, where the effect is positive (unidirectional). The regression coefficient of patient safety target variable (B2) is known as 0,551 indicating the influence of patient safety target variable on patient satisfaction. The result of the regression coefficient means that the patient's safety goal has an effect of 0.551 on patient satisfaction, where the effect is positive (unidirectional). Service quality variable partially significant to patient satisfaction and patient safety target variable partially significant to patient satisfaction. The hypothesis that the quality of service (X1) and patient safety goals (X2) simultaneously have a significant effect on patient satisfaction in this research is acceptable. The standardized beta coefficient value of the target patient's safety variable is greater than the standardized beta coefficient beta value of service quality variables. These results mean that the patient's safety goal is a variable that has a dominant effect on patient satisfaction. Value of correlation coefficient (r) equal to 0,904. This shows a positive and strong relationship between service quality variables and patient safety goals with patient satisfaction. Keywords: service quality, patient safety target, and patient satisfaction of Prima Husada Hospital